2010
DOI: 10.1007/s10334-010-0226-7
|View full text |Cite
|
Sign up to set email alerts
|

ADC measurements in the evaluation of lymph nodes in patients with non-Hodgkin lymphoma: feasibility study

Abstract: Object To determine whether apparent diffusion coefficient (ADC) measurements allow discrimination of normal lymph nodes from lymphomatous lymph nodes, and indolent lymphomas from aggressive lymphomas in patients with nonHodgkin lymphoma (NHL). Materials and methods Eighteen healthy volunteers and thirty-two patients with newly diagnosed NHL (indolent: n = 16; aggressive: n = 16) underwent diffusion-weighted imaging. ADCs of normal lymph nodes were compared to those of lymphomatous lymph nodes, and ADCs of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
(62 reference statements)
6
20
0
Order By: Relevance
“…ADC values of indolent lymphoma were lower than aggressive lymphoma, but the difference was not statistically significant. 20 The present results support the theory that increased cellular density contributes to more restricted diffusion; however, the ADC value is not merely dependent on tissue cellularity. Rather, other factors, such as cellular size and structure, extracellular matrix, and viscosity are also contributing factors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…ADC values of indolent lymphoma were lower than aggressive lymphoma, but the difference was not statistically significant. 20 The present results support the theory that increased cellular density contributes to more restricted diffusion; however, the ADC value is not merely dependent on tissue cellularity. Rather, other factors, such as cellular size and structure, extracellular matrix, and viscosity are also contributing factors.…”
Section: Discussionsupporting
confidence: 89%
“…Despite this, there were no significant differences in their mean ADC value. 19 Another study, by Kwee et al, 20 reported a significantly lower ADC value of lymphoma lesions in comparison to normal lymph nodes. ADC values of indolent lymphoma were lower than aggressive lymphoma, but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, the increased cellularity in FL contributes to more restricted diffusion, which also reduce the ADC value [18,24]. Our result consists with a recent study in patients with different subtypes of NHL [25], which showed that ADC measurement was no utility in differentiating indolent from aggressive lymphomas. However, the cellularity was not evaluated in that study.…”
Section: Discussionsupporting
confidence: 70%
“…The MRI techniques have been improved and new techniques, such as DW-MRI and new MRI sequences, have been developed in recent years. However, it is still difficult to distinguish between DLBCL and FL on the basis of MR image findings (3,4). Consistent with previous publications, we did not detect any significant difference in the ADC value between DLBCL and FL groups.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, DWI has been introduced as a new imaging modality that provides both morphological and functional information regarding characterization of lymphomas, and it has been used in detecting and staging malignant lymphomas, as well as in monitoring the response to therapy (1,2). However, it could not distinguish between diffuse large B-cell lymphoma (DLBCL) and follicular lymphoma (FL) (3,4). Positron emission tomography with the use of 2-deoxy-2-[ 18 F]fluoro-dglucose tracer could differentiate aggressive from indolent lymphoma and guide biopsies in the detection of histological transformation of indolent lymphoma (5,6).…”
Section: Introductionmentioning
confidence: 99%